(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The concept of discourse, the development of it, various approaches to its research in many spheres, the findings of experts on the study of discourse, and an assessment of the significance and varieties of modern discourse are all covered in this article.